A Hydrogel Bridge Incorporating Immobilized Growth Factors and Neural Stem/Progenitor Cells to Treat Spinal Cord Injury. Issue 7 (23rd February 2016) - Li, Hang; Ham, Trevor R.; Neill, Nicholas; Farrag, Mahmoud; Mohrman, Ashley E.; Koenig, Andrew M.; Leipzig, Nic D.
Abstract : Spinal cord injury (SCI) causes permanent, often complete disruption of central nervous system (CNS) function below the damaged region, leaving patients without the ability to regenerate lost tissue. To engineer new CNS tissue, a unique spinal cord bridge is created to deliver stem cells and guide their organization and development with site‐specifically immobilized growth factors. In this study, this bridge is tested, consisting of adult neural stem/progenitor cells contained within a methacrylamide chitosan (MAC) hydrogel and protected by a chitosan conduit. Interferon‐γ (IFN‐γ) and platelet‐derived growth factor‐AA (PDGF‐AA) are recombinantly produced and tagged with an N‐terminal biotin. They are immobilized to streptavidin‐functionalized MAC to induce either neuronal or oligodendrocytic lineages, respectively. These bridges are tested in a rat hemisection model of SCI between T8 and T9. After eight weeks treatments including chitosan conduits result in a significant reduction in lesion area and macrophage infiltration around the lesion site ( p < 0.0001). Importantly, neither immobilized IFN‐γ nor PDGF‐AA increased macrophage infiltration. Retrograde tracing demonstrates improved neuronal regeneration through the use of immobilized growth factors. Immunohistochemistry staining demonstrates that immobilized growth factors are effective in differentiating encapsulated cells into their anticipated lineages within the hydrogel, while qualitatively reducing glial fibrillary acid protein expression. Abstract : In this study, the safety and feasibility of a growth‐factor immobilized hydrogel bridge for spinal cord repair are investigated. The bridge is formed from methacrylamide chitosan with encapsulated neural stem/progenitor cells and protected with a chitosan conduit. Site‐specifically tethered growth factors within the hydrogel matrix successfully specify encapsulated stem cell lineages while improving retrograde tracing without adversely affecting macrophage infiltration.